Genetic variation analysis between wild and cultured pangasianodon hypopthalmus using COI and cytochrome b among Asian Countries / Nik Azwarina R Azmi ...[et al.] - R Azmi, Nik Azwarina; Ahmad, Lyena Watty Zuraine; Syed Mohamad, Sharifah Aminah; Zakaria, Nurul Aili; Mohamed Yunus, Norfatimah; Kambol, Roziah; Aris, Farizan (Universiti Teknologi MARA, 2022)
One of the top species in the aquaculture sector, known as striped catfish or Pangasianodon hypophthalmus, is an important and valuable freshwater fish in many countries. Due to the high demand for this species, their number has declined to "threatened" levels. Hence, the purpose of this study is to analyse the genetic variation of wild and cultured striped catfish collected from five producers in Asian countries; Thailand, Vietnam, Indonesia, India, and Philippines, by using mitochondrial DNA partial region data sequence; CO1 and cytochrome b gene. Population analyses using 395 base pairs length for CO1 and 275 base pairs length of cytochrome b partial region nucleotide sequence have shown no significance difference between wild and cultured striped catfish. Vietnam species had shown a wide range of genetic distance of the intrapopulation compared with other countries in the range of 0.000-0.040 for CO1 gene and 0.003-0.008 for cytochrome b gene. The Neighbour-joining method has also been used to construct phylogenetic trees using CO1 gene; the tree formed few subclades with mixed populations, and the tree using cytochrome b showed only Vietnam species divided into a few sub-populations. For the other four countries, Thailand, Indonesia, India, and Philippines were in the same group. Hence, this study's findings may provide a reference for inter and intra-relationships of P. hypophthalmus that may help in the aquaculture activity of this striped catfish.